1998
DOI: 10.1021/ac980390w
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Membrane Chromatography of Supercoiled Plasmid DNA

Abstract: Membrane adsorbers are well established in protein chromatography. The present paper investigated for the first time the behavior of polynucleotides on these stationary phases, taking a 7.2-kb predominantly supercoiled plasmid as example. Gradient and isocratic elution was studied. In contrast to protein high-performance membrane chromatography (HPMC), isocratic elution is possible in DNA chromatography. In the case of gradient elution, much higher salt concentrations can be used in the starting buffer. Under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 14 publications
0
47
0
Order By: Relevance
“…The analysis of large plasmid molecules by HPMDC has been discussed in a recent paper by Giovannini et al [69]. A 7.2-kb predominantly supercoiled plasmid was taken as example.…”
Section: Miscellaneousmentioning
confidence: 99%
“…The analysis of large plasmid molecules by HPMDC has been discussed in a recent paper by Giovannini et al [69]. A 7.2-kb predominantly supercoiled plasmid was taken as example.…”
Section: Miscellaneousmentioning
confidence: 99%
“…They found that increasing the flow rate by fourfold did not affect the membrane efficiency; however, increasing the flow rates caused a loss in resolution. Further, the authors were not successful in resolving various isoforms of DNA (Giovannini et al, 1998).…”
Section: Introductionmentioning
confidence: 97%
“…These reviews discuss almost exclusively the separation of proteins on membrane adsorbents. By contrast, the body of literature addressing the chromatography of much larger DNA and virus-like molecules using membranes is scarce (Giovannini et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Together with monoliths (Bencina et al 2004;Branovic et al 2004;Jungbauer and Hahn 2004;Urthaler et al 2005), other new supports have been developed to overcome the diffusion limitation as well as to improve the binding capacity of the support for the target molecules. Such superporous supports (Gustavsson et al 1999;Tiainen et al 2007b), and adsorptive membranes (Giovannini et al 1998;Teeters et al 2003) are advanced approaches that have been shown to be able to partially solve the problems associated with low capacity.…”
Section: Chromatographic Perspectives Enhancing Pdna Purificationmentioning
confidence: 99%